Image and media discourse of animal rights in spain: The Law on the Protection, Rights and Welfare of Animals in the general and specialised press - Rivera-Martín, Beatriz (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
Analysis of the image and discourse of Spanish press publications on the Animal Protection, Rights and Welfare Law. Using a mixed methodology based on content analysis, image analysis and critical discourse analysis, a total of 103 publications from general and specialised media have been analysed, in which it is clear that there is little social interest in the subject and the radicalism of the media that reject the law and are in favour of hunting, even threatening the promoters of the law with intimidating photomontages and hate speech.